Potential for injury from different life stages of Diceraeus melacanthus and Euschistus heros (Hemiptera: Pentatomidae) on corn seedlings - Bueno, N. M. [UNESP]; Baldin, E. L. L. [UNESP]; Melotto, G. [UNESP]; Silva, I. F.; Santos, T. L. B. [UNESP]; Ribeiro, L. P.; Koch, R. L. (Springer, 2021)
Changes in Brazilian corn production practices, have favored stink bugs, which feed on corn seedlings. Diceraeus melacanthus (Dallas) (Hemiptera: Pentatomidae), is a key pest in corn, and Euschistus heros (F.) (Hemiptera: Pentatomidae) is an emerging threat to corn. Economic thresholds (ET) for management of stink bugs are usually calculated based on the injury caused by adults. However, little is known about the impact of stink bug nymphs on corn seedlings. Thus, this work evaluated the effects of infestation with different nymphal instars on corn seedling weight (fresh and dry), plant height and stalk diameter. We also classified the level of overall injury to the seedlings using a rating scale. Corn seedlings in the V3 stage were infested with two insects of either D. melacanthus or E. heros in the 2(nd), 3(rd), 4(th), 5(th) instars or adult stage in separate greenhouse studies performed for each species. Plants without infestation were used as controls. Both species of stink bugs feeding on corn seedlings affected all the assessed parameters. The quantitative measures of seedling size (i.e., fresh weight, dry weight, plant height and stem diameter) were generally most severely affected by the 5(th) instars and adults of D. melacanthus and the 4(th) instars of E. heros. The qualitative injury rating scale generally showed a greater impact to seedlings by 3(rd) instar to adult life stages of each species. Across life stages, injury to seedlings caused by D. melacanthus was numerically greater than that from E. heros. These results will guide the development of a more accurate ETs for stink bug management on seedling corn plants.
Keywords: Zea mays L; Green belly stink bug; Neotropical brown stink bug; Nymphal injury